Mural paintings deterioration – a multianalytical approach - Rosado, T (2016)
This work presents a novel microanalytical approach in the mural paintings microbial diversity characterisation and identification of the damages promoted by their biological activity. Mortar microfragments, removed from visually biodegraded mural paintings, were analysed by several microscopic/spectroscopy techniques: variable pressure scanning electron microscopy coupled with energy dispersive X-ray spectrometry (VP-SEM-EDS), raman microspectrometry and infrared spectrometry in order to evaluate the presence of microbial contamination and to detect the alteration products resulting from the metabolic activity of the microorganisms. These analyses were complemented with culture-dependent methods and DNA based approaches